2009
DOI: 10.1113/jphysiol.2008.163337
|View full text |Cite
|
Sign up to set email alerts
|

An internal model of a moving visual target in the lateral cerebellum

Abstract: In order to overcome the relatively long delay in processing visual feedback information when pursuing a moving visual target, it is necessary to predict the future trajectory of the target if it is to be tracked with accuracy. Predictive behaviour can be achieved through internal models, and the cerebellum has been implicated as a site for their operation. Purkinje cells in the lateral cerebellum (D zones) respond to visual inputs during visually guided tracking and it has been proposed that their neural acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 71 publications
10
92
0
Order By: Relevance
“…A recent study in cats showed that neuronal discharge in the lateral cerebellum was predictive of target motion 110 ; the authors speculated that such activity could be used in a predictive capacity for target interception. This result might plausibly be extrapolated to an athlete predicting the effect of an opponent's motion on ball trajectory.…”
Section: Box 1: Forward Modelsmentioning
confidence: 99%
“…A recent study in cats showed that neuronal discharge in the lateral cerebellum was predictive of target motion 110 ; the authors speculated that such activity could be used in a predictive capacity for target interception. This result might plausibly be extrapolated to an athlete predicting the effect of an opponent's motion on ball trajectory.…”
Section: Box 1: Forward Modelsmentioning
confidence: 99%
“…Cerebellum has the ability to encode and decode the timing and target trajectories for predictive pursuit (Cerminara et al 2009;Kettner et al 1997;Lisberger 2008, 2009;Suh et al 1997Suh et al , 2000, and partial ablations of the cerebellum cause deficits in smooth pursuit and VOR adaptation (Rambold et al 2002). To our knowledge, no electrophysiological evidence for retinal neuronal reference frames exists in cerebellar neurons, therefore making it unclear whether cerebellum could encode and maintain a retinal velocity memory.…”
Section: Hypothetical Underlying Neurophysiologymentioning
confidence: 93%
“…In support of the first hypothesis, many studies have pointed to the cerebellum because of its involvement in motor learning and in predictive pursuit tasks (Cerminara et al 2009;Kettner et al 1997;Lisberger 2008, 2009;Suh et al 1997Suh et al , 2000. Cerebellum has the ability to encode and decode the timing and target trajectories for predictive pursuit (Cerminara et al 2009;Kettner et al 1997;Lisberger 2008, 2009;Suh et al 1997Suh et al , 2000, and partial ablations of the cerebellum cause deficits in smooth pursuit and VOR adaptation (Rambold et al 2002).…”
Section: Hypothetical Underlying Neurophysiologymentioning
confidence: 99%
“…For example Wolpert et al (1995) claim that in many cases action is goal-directed and supported by internal models. Moreover, there is a vast literature that show how prediction and internal models play an important role in (visuo)motor control (Kawato, 1999;Miall and Wolpert, 1996) and in the stabilization of perception (von Holst and Mittelstaedt, 1950), allow to circumvent the problems caused by the delay with which sensory information reach the central nervous system (during the execution of fast reaching movements (Cerminara et al, 2009;Desmurget and Grafton, 2000) or during walking and posture control behavior (von Hofsten, 2004)), and allow to cancel self-produced stimuli so to focus the attention on relevant external stimuli (Webb, 2004). The idea of internal modeling is not confined to the motor domain but it is increasingly being used as a unifying concept that relates sensorimotor, cognitive and social abilities, including for example off-line motor planning, motor imagery, reasoning, imitation, mindreading, and cooperation (Frith et al, 2000;Grush, 2004;Jeannerod, 2006;Pezzulo, 2011;Schubotz, 2007;Wolpert et al, 2003).…”
Section: Introductionmentioning
confidence: 99%